Impact of dietary cadmium sulphide nanoparticles on Danio rerio zebrafish at very low contamination pressure. Issue 6 (September 2014) - Ladhar, Chiraz; Geffroy, Benjamin; Cambier, Sébastien; Treguer-Delapierre, Mona; Durand, Etienne; Brèthes, Daniel; Bourdineaud, Jean-Paul
Abstract To address the impact of cadmium sulphide nanoparticles (CdSNPs) of two different sizes (8 and 50 nm), Danio rerio zebrafish were dietary exposed to very low doses: 100 or 40 ng CdSNPs/day/g body weight for 36 or 60 days, respectively. The results obtained using RAPD-PCR genotoxicity test showed genomic alteration since the number of hybridisation sites of the RAPD probes was significantly modified after CdSNPs exposure. In addition, selected stress response genes were either repressed or upregulated in tissues of CdSNPs-exposed fish. Mitochondrial dysfunction was also caused by the presence of CdSNPs in food. Cadmium accumulation in fish tissues (brain and muscles) could only be observed after 60 days of exposure. CdSNPs toxicity was dependent on their size and concentration.